Occupational Therapy for Parkinsonian Patients: A Retrospective Study - Michele Franciotta; Roberto Maestri; Paola Ortelli; Davide Ferrazzoli; Federica Mastalli; Giuseppe Frazzitta (Parkinson's Disease)
Background. Hand functionality and finger dexterity are impaired in patients with Parkinson’s disease (PD). These disturbances lead to a dependency in activities of daily living (ADL) and poor quality of life (QoL). Objective. We aimed to evaluate whether a specific occupational therapy (OT) program is effective in improving finger and hand dexterity and its impact on ADL in PD patients. Methods. We retrospectively studied PD patients, hospitalized for a 4-week multidisciplinary intensive rehabilitation treatment (MIRT) between January 2015 and June 2018. All patients underwent 1 h/day OT treatment, 5 days a week. The primary outcome measure was the O’Connor finger dexterity test; secondary outcome measures were the Minnesota dexterity test, UPDRS II, and Self-Assessment Parkinson’s Disease Disability Scale (SPDDS). These measures were assessed at admission (T0) and discharge (T1). Results. Based on the Hoehn and Yahr scale (H&Y), patients were divided into two groups: 262 subjects in H&Y stage <3 (early-stage PD patients) and 220 in H&Y stage ≥3 (medium-advanced stage PD patients). As expected, at baseline, all measures were worse in higher H&Y stages. After treatment, both groups experienced significant improvements in all outcomes. Significant differences between early-stage and medium-advanced stage PD patients were observed only for the changes in UPDRS II, with a better improvement in patients in H&Y stage ≥3. Conclusions. We showed that PD patients who underwent a rehabilitation protocol including OT experienced improvements in finger dexterity and hand functionality. Our results underline the relevance of OT in improving autonomy and QoL in PD patients.